LEGAL EVALUATION OF THE ASSIMILATION AND CONDITIONAL LEAVE PROGRAM FROM THE PERSPECTIVE OF PUNISHMENT OBJECTIVES - Siska Amelya; Rise Karmilia; Hendri; Darlisma (RADJA PUBLIKA, 2025)
Assimilation and conditional leave programs are two important instruments in the Indonesian correctional system, serving as a form of punishment outside of correctional institutions. This article evaluates the validity and effectiveness of these two programs from the perspective of modern sentencing objectives: retribution, deterrence, rehabilitation, and social reintegration. Using a normative juridical approach and policy analysis, this paper examines how assimilation and conditional leave are implemented and the extent to which they reflect the principles of justice and the effectiveness of criminal law. The study reveals that although normatively these programs support the goals of progressive sentencing, in practice, legal and administrative obstacles still exist that hinder the achievement of effectiveness and substantive justice.